Analysis of The Importance of Omnibus Law “Cipta Karya" in Indonesia - Harahap, Hadry; Hamid, Adnan (International Journal of Scientific Research and Management (IJSRM), 2020)
This study attempts to describe the juridical and historical aspects of the implementation of the Manpower Law, and this study aims to analyze the importance of the Omnibus Law "Cipta Karya" in Indonesia in Indonesia.. This research was conducted using descriptive and qualitative methods, through a library research approach. The results of this study indicate that the Omnibus Law “Cipta Karya” Bill was passed by the Indonesian Parliament. The bill is considered to have the potential to violate the rights of citizens guaranteed by the constitution because for the sake of investment, labor rights are secondary. Therefore, comprehensive and sustainable strategic efforts are needed to improve labor laws in Indonesia with reference to the mandate of Law Number 12 of 2011 in conjunction with Law Number 15 of 2019 concerning the Formation of Laws and Regulations that must contain consideration of aspects philosophical and juridical and sociological. Therefore, the Government and the House of Representative (Dewan Perwakilan Rakyat Republik Indonesia  - DPR RI)  must have a high commitment and political will in terms of the formation of labor laws and regulations based on the principles of clarity of objectives, the principle of appropriate institutional or forming organs. , the principle of clarity of formulation, and the principle of transparency